Comparison of the Actions of Thrombin and the Thrombin-Like Venom Enzymes Ancrod and Batroxobin - Aronson, D. L (Thrombosis and Haemostasis, 1976)
Thrombin acts on several coagulant proteins to produce products with physiologic, pharmacologic and pathologic potential. The most sensitive thrombin substrate seems to be factor VIII. Some thrombin dependent reactions studied in vitro and proposed as control reactions seem too insensitive to the action of thrombin to be of in vivo significance.The only enzymic reaction the thrombin-like venom enzymes, Ancrod and Batroxobin, have in common with thrombin is the removal of fibrinopeptide A.